(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Uzbekistan, as one of the key countries in Central Asia, is distinguished by its ancient historical monuments, rich culture, and unique natural landscapes. The country's tourism potential is increasingly significant not only in domestic tourism but also in the international arena. Uzbekistan is renowned worldwide for its historical cities, architectural landmarks, national culture, and traditions. This scientific article provides an analytical overview of Uzbekistan's tourism potential, development factors, challenges, and prospects.